Hambatan Online Learning terhadap Motivasi Belajar Mahasiswa Keperawatan di Masa Pandemi Covid-19 - Mardiah Mardiah; Sintiya Halisya Pebriani; Lily Marleni (Universitas Malahayati Lampung, 2022)
ABSTRACT Online learning as a step to prevent the spread of the Covid-19 virus has turned out to be a burden in itself and requires adaptation and effort to run well. This learning method has been implemented in almost all universities in Indonesia, but in fact it is still not fully running well, so it can have an impact on learning motivation. This research was conducted to determine the effect of online learning on students' learning motivation. The research design used descriptive correlation with a cross sectional approach. The research sample with a total sampling of 113 respondents. Data was collected using an online-based questionnaire distributed via a google form link consisting of an online learning barrier questionnaire and a learning motivation questionnaire. The research data were analyzed using univariate and bivariate analysis using Spearman Rank (Rho) with 95% confidence level (α = 0.05). Based on the results of the analysis, it was found that most of the respondents experienced severe category barriers in online learning, namely 44 (39%) respondents, 62 (55%) respondents in the moderate category, and only 7 (6%) in the mild category. The level of student learning motivation in online learning mostly has strong motivation, namely as many as 62 respondents (54.96%), medium motivation 46 respondents (40.7%) and low motivation as many as 5 respondents (4.4%). The results of the Spearman Rank (Rho) test showed the effect of online learning on student learning motivation during the covid-19 pandemic (p = 0.000) with a value of r = -0.442 which indicates a fairly strong and opposite relationship. There is an influence of online learning constraints on student learning motivation during the covid-19 pandemic. This is due to the various problems experienced by both teachers and students in the online learning process. When the level of online learning obstacles is increasingly felt by students, it will further reduce the student's learning motivation. Keyword: Online Learning, Learning Motivation, Covid-19 ABSTRAK Pembelajaran online sebagai langkah pencegahan penyebaran virus Covid-19 ternyata menjadi beban tersendiri dan membutuhkan adaptasi serta usaha agar dapat berjalan dengan baik. Metode pembelajaran ini telah dilaksanakan dihampir seluruh perguruan tinggi di Indoensia, namun ternyata masih belum sepenuhnya berjalan dengan baik, sehingga dapat berdampak pada motivasi belajar. Penelitian ini dilakukan untuk mengetahui pengaruh pembelajaran online terhadap motivasi belajar mahasiswa. Desain penelitian menggunakan deskriptif korelasi dengan pendekatan cross sectional. Sampel penelitian dengan total sampling yang berjumlah 113 responden. Pengumpulan data dilakukan dengan kuesioner berbasis online yang di sebarkan melalui link google form yang terdiri dari kuesioner hambatan pembelajaran online dan kuesioner motivasi belajar. Data hasil riset di analisis secara univariat dan bivariat dengan menggunakan analisis Spearman Rank (Rho) dengan derajat kepercayaan 95% (α = 0,05). Berdasarkan hasil analisis didapatkan sebagian besar responden mengalami hambatan kategori berat dalam pembelajaran online yaitu sebanyak 44 (39%) responden, kategori sedang sebanyak 62 (55%) responden, dan hanya 7 (6%) dalam kategori ringan. Tingkat motivasi belajar mahasiswa pada pembelajaran online sebagian besar meiliki motivasi kuat yaitu sebanyak 62 respoden (54,96%), motivasi sedang 46 responden (40,7%) dan motivasi rendah sebanyak 5 responden (4,4%). Hasil uji Spearman Rank (Rho) didapatkan pengaruh pembelajaran online terhadap motivasi belajar mahasiswa di masa pandemi covid-19 ( p=0,000) dengan nilai r = -0,442 yang menunjukkan hubungan cukup kuat dan berlawanan. Terdapat pengaruh kendala pembelajaran online terhadap motivasi belajar mahasiswa di masa pandemi covid-19. Hal ini disebabkan berbagai problematika yang dialami baik oleh para pengajar maupun pelajar dalam pelaksanaan pembelajaran online. Ketika tingkat kendala pembelajran online semakin berat dirasakan oleh mahasiswa maka akan semakin menurunkan motivasi belajar mahasiswa tersebut. Kata Kunci: Pembelajaran Online, Motivasi Belajar, Covid-19